Prevalence and Resistance Profile of Enterobacteriaceae Isolates from Urine Samples at the Laboratory of Regional Public Hospital Institution (EPHR) from January to May 2026 - Traore Youssouf Zanga; Gadou Victoire; N’guessan Loukou Séraphin; Kouadio; Nathalie Guessend (Microbiology Research Journal International, 2026)
Background: Multidrug resistance refers to the ability of bacteria to withstand multiple classes of antibiotics, complicating antibiotic therapy. In clinical practice, it is therefore crucial to understand the resistance profiles of the pathogens commonly implicated in specific conditions to avoid contributing to the emergence of this phenomenon. Aim: This study assessed the prevalence of urinary tract infections and characterised the resistance profiles of Enterobacteriaceae isolated from urine samples received at Korhogo Regional Hospital from January to May 2026 Methods: Collected urine samples were preserved using boric acid and sodium formate. Following macroscopic analysis, microscopic examination was performed using a 40x objective. Bacterial colonies were isolated using a 1:100 urine dilution technique and inoculation onto selective media. Gram staining and standard biochemical test strips were then used to identify Enterobacteriaceae. Finally, the Vitek 2 automated system was used to perform antimicrobial susceptibility testing on a bacterial inoculum prepared from one or two colonies, distilled water, and 0.9% NaCl. Results: The results revealed a urinary tract infection prevalence of 74% among the 86 samples studied. Regarding the sex distribution, the prevalence was 43.75% among males and 56.25% among females. Gram staining revealed a predominance of bacteria. The prevalence of Enterobacteriaceae was 34.88%, with a high prevalence of E. coli (70%), followed by Klebsiella (26.67%) and Enterobacter (3.33%) among the 30 identified urinary tract infections. Antibiotic susceptibility testing revealed bacterial resistance to more than 15 of the tested antibiotics. Only imipenem and amikacin proved effective against the Enterobacteriaceae, with a minimum inhibitory concentration (MIC) of 4 micrograms per millilitre or less. Conclusion: Considering these results, it is important to note the risk of multidrug-resistant infections in cases of urinary tract infection. Consequently, clinicians must exercise rigour in the prescription and use of antibiotics.